Acute and chronic hyponatremia: A narrative review (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Hyponatremia is an important electrolyte abnormality with the potential for significant morbidity and mortality. Catastrophic complications can occur from severe acute hyponatremia and from inappropriate management of acute and chronic hyponatremia. It is essential to define the hypotonic state associated with hyponatremia in order to plan therapy. Understanding cerebral defence mechanisms to hyponatremia are key factors to its manifestations and classification and subsequently to its management. Hypotonic hyponatremia is differentiated on the basis of urine osmolality, urine electrolytes and volume status and its treatment is decided based on duration and central nervous system symptoms. Proper knowledge of sodium and water homeostasis is essential in individualizing therapeutic plans and avoiding iatrogenic complications while managing this disorder.J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2): 58-65